(untitled) (American Journal of Islam and Society, 2006)
In his book In Pursuit of Legitimacy, Hesham Al Awadi sets out to explain Egyptian president Mubarak’s dramatic shift in his treatment of the Muslim Brothers (Al Ikhwan Al Muslimin), from toleration of the outlawed group to severe repression, over the first two decades of his regime. Standard explanations for this shift, as Awadi points out, have a state-centric bias in which the state is the primary actor responding to the threat posed by the Muslim Brothers to the regime, either by providing social services when the state’s capacity to do so was hampered, or by challenging the legitimacy of an authoritarian regime. The author acknowledges these factors, but then offers a substantially different narrative in which he skillfully traces the political dance of power between the outlawed group and the regime. The move to repression, in Awadi’s rendering, can be better explained by the responsive relationship between the Muslim Brothers and Mubarak than by understanding either power or legitimacy solely in terms of the state. Awadi argues that the driving force behind Mubarak’s crackdown in the mid-1990s was a cyclical competition between the president and the Muslim Brothers for political legitimacy, which began with his regime’s accession following Sadat’s assassination in 1980. In his analysis, the author states that this conflict’s brutal 1995 climax, during which a number of Muslim Brothers were convicted at a military trial, was by no means a foregone conclusion. Rather, it was the result of a highly responsive relationship between the regime and the increasingly powerful opposition organization. Moreover, it could have evolved differently had the Muslim Brothers made different choices about how to best pursue their program ...